Theologies of women’s submission and the COVID-19 pandemic - Nomatter Sande (HTS Teologiese Studies/Theological Studies)
Women’s submissions to husbands are an accepted phenomenon in Africa and across the globe. The triad, Indigenous cultures, African Traditional Religions (ATR) and Christianity are the sources and shapes of theologies of women’s submission. Whenever cultural practices and religious theologies go hand in hand, people tend to regard such practices as par excellence and pay less attention to their negative impact. This article explores the dilemmas of women’s submissions in the coronavirus disease 2019 (COVID-19) pandemic in Zimbabwe. The article uses the Feminist theory as a theoretical framework to interpret the meaning of theologies of women’s submission in COVID-19. Data for this study were gathered through desktop research. The article concludes that the unprecedented emergence and challenges of global COVID-19 have further unmasked African women’s unique difficulties in society, especially on the much-celebrated practices of the theologies of submission. Women’s submission trapped women to be affected more by COVID-19 than their male counterparts.